2016
DOI: 10.1186/s13098-016-0140-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory data of a large series of patients with congenital generalized lipodystrophy

Abstract: BackgroundBerardinelli-Seip congenital lipodystrophy (BSCL) was initially described by Berardinelli in Brazil in 1954 and 5 years later by Seip in Norway. It is an autosomal recessive disease that leads to a generalized deficit of body fat, evolving with diabetes and hypertriglyceridemia. The aim of this study was to describe the clinical and laboratory characteristics of a large series of patients with BSCL.MethodsThis is a cross-sectional study of patients with BSCL. A total of 54 cases of BSCL were diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 30 publications
8
70
0
3
Order By: Relevance
“…In the Brazilian BSCL cohort, from the state of Rio Grande do Norte, there are very high prevalence rates of Type 2 as described previously [8] due to consanguineous marriages.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In the Brazilian BSCL cohort, from the state of Rio Grande do Norte, there are very high prevalence rates of Type 2 as described previously [8] due to consanguineous marriages.…”
Section: Introductionmentioning
confidence: 80%
“…These patients are part of a cohort previously published [8]. The mean age was 24.7±8.1 years old, and there were six females.…”
Section: Resultsmentioning
confidence: 99%
“…Globally, the most common mutation is the c.589-2A > G (rs116807569). In Brazil, the predominant CGL mutations are c.589-2A > G, c.317-588del, c.646A > T, and c.570C > A in the AGPAT2 gene [17][18][19]. Our historical relationship with Portugal and Africa during colonization and the previous description of the c.589-2A > G mutation in these locations suggest a founder effect (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Berardinelli-Seip congenital lipodystrophy (BSCL) is an autosomal recessive disease accompanied by lipodystrophy, diabetes, and hypertriglyceridemia, but muscle hypertrophy is among the most common clinical features of BSCL [9][10][11][12]17]. This study revealed that seipin deficiency led to uterine smooth muscle hypertrophy in middle-aged mice but not in the prepubertal mice.…”
Section: Discussionmentioning
confidence: 92%
“…We have been studying the functions of seipin in reproductive systems using seipin-deficient Bscl2 −/− mice and identified roles of seipin in mammary gland development, vaginal opening, and spermatogenesis [11,12]. Since seipin deficiency is associated with muscle hypertrophy and diabetes [10,17], diabetes has been associated with impairment of uterine contractility [18], and uterine smooth muscle contractions are critical for parturition, it was hypothesized that seipin deficiency might affect the myometrium to influence parturition. This hypothesis was tested in seipin-deficient Bscl2 −/− adult female mice.…”
Section: Introductionmentioning
confidence: 99%